Late Quaternary paleoseismic behavior and rupture segmentation of the Yingxiu‐Beichuan fault along the Longmen Shan fault zone, China. Issue 11 (19th November 2014) - Ran, Yongkang; Chen, Wenshan; Xu, Xiwei; Chen, Lichun; Wang, Hu; Li, Yanbao
Abstract Late Quaternary rupture behavior of large earthquakes along the Yingxiu‐Beichuan fault and the Longmen Shan fault zone has been the focus of geoscientists since the 2008 Wenchuan earthquake. However, most studies have concentrated on the southern segment of the fault from Yingxiu to Beichuan. Here we opened trenches and used borehole drilling in Guixi and Pingxi along the northern segment (north of Beichuan) with the following paleoseismic results: (1) Trenches at Pingxi and Guixi reveal that at least one paleoseismic event occurred prior to the 2008 Wenchuan earthquake with ages of 770–955 A.D. and 665–1030 A.D. determined at the two locations, respectively. This event is possibly associated with a historical earthquake documented from 16 November to 15 December of 942 A.D.; furthermore, the trench and boreholes at Guixi may reveal another paleoseismic event occurred at 8240–7785 B.C.; (2) the northern segment (north of Beichuan) of the seismogenic structure of the 2008 Wenchuan earthquake ruptured independently from the southern segment; specifically, the southern segment records three events within the past 6000 years, whereas the northern segment shows a different rupture behavior. We suggest that the Yingxiu‐Beichuan fault can be divided into at least two rupture segments.